The Use of Purik Leaf Extract (Mitragyna speciosa) on Hematological and Histopathological Profile of Vannamei Shrimp (Litopenaeus vannamei) on Vibrio Parahaemolyticus Infection - Sugiharta, Andreas; Fadjar, Moh; Hardoko, Hardoko (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to analyze the optimal dose of Purik leaf extract (Mitragyna speciosa) which has antibacterial compounds to treat vannamei shrimp (Litopenaeus vannamei) that infected by Vibrio parahaemolyticus. The method used in this research is experimental study with Completely Randomized Design (CRD). The results form GC-MS analysis of purik leaf extract showed that the most abundance compounds were Quinic acid and Mitragynine from flavonoid and alkaloid class.Â  Total Hemocytes Count (THC) after purik leaf treatment on vibrio infected vannamei shrimp showed that extract at 250 mg/L dose showed the best result with 8.03x106 cells/ml. The Differential Haemocyte Count (DHC) after treatment showed that the most effective dose is 250 mg/L with 20.33% hyaline, 23.67% semigranular cells, and 56% granular cells. Based on histopatology observation of vannamei hepatopancreas after treatment showed that the best dose is 250 mg/L with 1.20% haemorrhage, 1.20% necrosis, and 1.40% cell inflammation. Purik leaf extract which contains many compounds can be useful as an antibacterial to inhibit and destroy V. parahaemolyticus bacteria and proven to treat vannamei shrimp (L. Vannamei) that infected by V. parahaemolyticus